Efektivitas Program Penurunan Angka Stunting Di Desa Kalola Kecamatan Bambalamotu Kabupaten Pasangkayu - Saputra, Wahyudi Anugrah; Suasa; Rapi, Muhammad (JPS: Journal of Publicness Studies, 2026)
Stunting remains a major public health challenge in Indonesia due to its long-term impact on children's growth, development, and future human resource quality. To address this issue, the government has implemented various stunting reduction programs through nutrition-specific and nutrition-sensitive interventions involving multiple levels of administration. This study aims to examine the effectiveness of the Stunting Reduction Program in Kalola Village, Bambalamotu District, Pasangkayu Regency. This research employed a qualitative descriptive approach. Data were collected through observation, interviews, and documentation involving six key informants, including representatives from the Health Office, village government, community leaders, health workers, and the Family Welfare Empowerment (PKK) organization. The data were analyzed through data reduction, data presentation, and conclusion drawing. The findings indicate that the program has not yet achieved optimal effectiveness. Based on Campbell’s effectiveness framework, only the target achievement indicator was considered effective, as assistance and interventions were delivered to the intended beneficiaries. In contrast, the indicators of program success, participant satisfaction, input-output performance, and overall goal attainment were found to be less effective. Several factors contributed to these outcomes, including limited community participation in counseling and recovery activities, inadequate awareness of nutrition and healthy lifestyles, and the persistence of traditional practices among some community members. Furthermore, the prevalence of stunting in Kalola Village fluctuated from 26.86% in 2022 to 25.08% in 2023, before increasing to 27.43% in 2024. Strengthening community engagement, health education, and cross-sector collaboration is therefore essential to improve the effectiveness and sustainability of stunting reduction efforts.